Relevansi Teori Hukum Progresif dalam Upaya Reformasi Sistem Peradilan Pidana di Indonesia - Darlipius Buulolo; Padrisan Jamba (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the relevance of progressive legal theory in the reform of Indonesia’s criminal justice system from normative, philosophical, and legal policy perspectives. This research employs a qualitative library-based method using a juridical-normative and conceptual approach to examine progressive legal theory and its implications for criminal justice practices. The findings indicate that progressive legal theory has strong relevance as a framework for criminal justice reform, as it emphasizes substantive justice, contextual legal reasoning, and a human-centered orientation. Consequently, progressive legal theory offers a normative and philosophical foundation for promoting a more responsive, humane, and just criminal justice system in Indonesia.